IMPROVING THE TECHNOLOGY OF LIQUIDATION OF WEAR – RESISTANT WHITE CAST IRON - Saidmakhamadov Nosir; Turakhodjaev Nodir; Abdullaev Kamol; Saidkhodjaeva Shokhista; Tadjiev Nuritdin (International Journal of Innovations in Engineering Research and Technology, 2022)
In this article, the optimal mode of liquefaction of wear – resistant white cast iron alloy in an induction furnace is developed. In addition, the chemical composition of the alloy for wear – resistant white cast iron without reducing the mechanical properties was developed, which is cheap and resource – saving from the economic point of view, and the microstructures of the alloy were examined using a scanning electron microscope.Also, depending on the amount of carbon and chromium in the alloy, the fluidity of the alloy was determined, and quality cast products were obtained.